2016
DOI: 10.15593/2224-9923/2016.19.8
|View full text |Cite
|
Sign up to set email alerts
|

Development of the technology for conservation of spoil heaps in order to reduce its negative impact on the environment and preserve resource potential

Abstract: Coal mining is accompanied by bulk waste formation in form of spoil heaps from low quality ore. As a result of aggressive natural factors impact specific mineral and chemical composition of rocks, which forms spoil heaps, leads to the environmental man-caused load in form of dust and gas emission, water pollution and adjacent area littering. Thus, lands, where spoil heaps are disposed, are excluded from economic use, and their resource potential gets lost because of wind and water erosion, negative physical, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Bentomat structure is shown in Fig. 4 [19]. Bentonite mats are produced by such companies as NAUE (Germany), HUESKER (Germany), GSE (Germany), Tehstroyteks (Belarus), CETCO (Poland), Carpi (Switzerland), ISOBENT (Belarus), BentIzol (Russia), Nilex (Canada) and others.…”
Section: Spoil Heaps Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bentomat structure is shown in Fig. 4 [19]. Bentonite mats are produced by such companies as NAUE (Germany), HUESKER (Germany), GSE (Germany), Tehstroyteks (Belarus), CETCO (Poland), Carpi (Switzerland), ISOBENT (Belarus), BentIzol (Russia), Nilex (Canada) and others.…”
Section: Spoil Heaps Conservationmentioning
confidence: 99%
“…That is especially important because mechanical damage is possible during transportation and installation of the material. It was found that bentonite mats filled with sodium are most technology efficient from that group of waterproof materials, because they have the best penetration coefficient values [19].…”
Section: Spoil Heaps Conservationmentioning
confidence: 99%